Karst Ecosystem Restoration in the Nglirip Cave Nature Reserve with Endemic Plants - Andrea Stevens KARNYOTO; Yunan KURNIAWAN; Rahayu Eka SARI; Nauvani Rahma ILAHI; Citra Asmo MARDHIATI; Asharviyan Ridzky HERMAWAN; Munirul ICHWAN; Charnia Iradat RAPA; Indo INTAN (PT Keberlanjutan Strategis Indonesia, 2025)
The karst ecosystem of the Nglirip Cave Nature Reserve in Tuban Regency, East Java, plays a vital role as a water reservoir, carbon sink, and biodiversity hub. However, uncontrolled deforestation and human activities have disrupted the ecological balance, threatening the flora and fauna, as well as the local groundwater reserves. This study documents a collaborative restoration program initiated by PT PLN Nusantara Power Unit Pembangkit Tanjung Awar-Awar (UPTA), in partnership with the East Java BBKSDA (National Resources Conservation Agency) and the Tuban Regency Environmental Agency. The program aimed to rehabilitate the karst ecosystem through the planting of 1,000 endemic trees, which are Ficus benjamina and Ficus macrocarpa. These trees were chosen for their high-water absorption capacity and ecological suitability to the Nglirip Cave Nature Reserve. We implemented an innovative protection technique called “Ficus in Shield” by constructing cylindrical galvanized sheet metal under the tree trunks. This procedure was implemented to protect the saplings from damage by porcupines. The results show a measurable increase in biodiversity, evidenced by an increase in the Shannon-Wiener Biodiversity Index, and are expected to improve groundwater retention and ecosystem resilience. Beyond the ecological benefits, this initiative emphasizes the importance of public-private collaboration in biodiversity conservation and climate resilience. These findings highlight that endemic-based reforestation, combined with adaptive protection methods, is expected to effectively restore longdegraded karst ecosystems and serve as a model for sustainable conservation both in the Nglirip Cave Nature Reserve and elsewhere.